Learning Model for Basic Manipulative Movements Using Si Buyung Gymnastics: Enhancing Movement Skills in Children with Mild Disabilities - Nur Rohmah, Laila; Lufthansa, Luthfie; Artanty, Ary; Dwi Pradipta, Galih; Munir, Ali (Journal of Education Technology, 2024)
SLB students, including students with mild special needs, it was found that students had difficulties in mastering basic manipulative movement skills. These obstacles were seen when students did activities that involved interaction with objects, such as throwing, catching, or dribbling the ball. Based on this, this study aimed to produce an effective learning model to develop basic motor skills, such as manipulative, locomotor, and stability movements. This study involved needs analysis, design, trial, revision, and model implementation. The subjects were students with mild mental retardation in SLB, selected based on their motor limitations. Data were collected by observing and measuring motor skills before and after applying the model. The analysis used quantitative and qualitative approaches. The results showed that this model significantly improved students' basic motor skills. This model increased student motivation, participation, and skills by using simple, repetitive, and game-based movements. These findings support the implementation of the Senam Si Buyung-based learning model in SLB as part of the physical education curriculum, providing a positive impact on the physical, social, and emotional development of children with mild mental retardation. This research implies that this learning model provides a comprehensive and applicable framework for teachers to assist students with special needs in optimizing students' movement potential.